1998
DOI: 10.1159/000028237
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Activity of Two Pt(IV) Salts against <i>Leishmania donovani</i>

Abstract: The activities of 8 platinum drug complex salts were determined against Leishmania donovani promastigotes. The three most active salts were selected: [PtIVBr6]H2 (pentamidine); [PtIVBr6]H2 (stilbamidine), and [PtIVCl6]H2 (2-piperazinyl(1) ethyl amine), which induced growth-inhibition rates of more than 50% at 24 h of treatment and at the maximum dosage tested. The cytotoxicity assays on the macrophage cell line J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In addition, Steck [30] observed that the combination of pentamidine with anionic compounds gave rise to complexes with stronger prophylactic activity against the African trypanosomes. Also other authors [31] demonstrated the antileishmania activity of some Pt(IV) complexes.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, Steck [30] observed that the combination of pentamidine with anionic compounds gave rise to complexes with stronger prophylactic activity against the African trypanosomes. Also other authors [31] demonstrated the antileishmania activity of some Pt(IV) complexes.…”
Section: Discussionmentioning
confidence: 86%
“…Metal compounds have been shown to have anti-parasitic properties in models of parasitic disease [23][24][25][26][27][28][29][30][31], and the antimonial drugs are still first line treatment for leishmaniasis [2]. However the molecular mechanism of these metal compounds is undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Several metal complexes have been reported to have anti-parasitic activity such as gold(I) phosphine and chloroquine complexes [23][24][25], platinum(II) and (IV) complexes [26][27][28][29] and organometallic complexes of iridium, rhodium, palladium and osmium [29][30][31] against a variety of trypanosomatids. Though there is evidence to suggest that these complexes target organelles such as the nucleus and kinetoplast [27][28][29][30][31], the molecular target of these compounds has not been defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include mostly the nitrogen heterocycles; quinolines, 9 acridines, 10 phenothiazines, 11 pyrimidines 12 and purines; 13 and many other class of compounds including anilines, 14 flavonoids, 15 quinones, 16 amino acid esters and amides, 17 amino alcohols, 18 alkyl phospholipids, 19 and certain Pt complexes. 20 Development of most active and selective chemotherapeutic agents could be achieved by rational drug design taking into consideration the biochemical machinery of the parasite. Protozoan parasites of the genus Leishmania are prone to oxidative stress or oxidative siege from various ROS.…”
Section: Introductionmentioning
confidence: 99%